Who cares for syphilis? A cross- sectional study on diagnosis and treatment of syphilis by GPs in Amsterdam, the Netherlands. Issue 2 (June 2020) - , Michel Baas; Beers, Erna; Dam, Alje P van; Bergen, Jan EAM van
No abstract available